AgriTech4Egypt Innovation Challenge: Bootcamp report - Zaccari, Claudia (Bioversity International and International Center for Tropical Agriculture, 2024)
The AgriTech4Egypt Innovation Challenge 2024 is a project designed to empower talented innovators and accelerate the development, deployment, and adoption of early-stage agri-tech solutions that can create a more sustainable, efficient, and climate-resilient agriculture in Egypt, while aligning with the country’s 2030 Sustainable Agricultural Development Strategy and Sustainable Development Goals (SDG). This project attracted 975 applications from 48 countries, from which 25 teams were selected for a bootcamp in Belbeis. This immersive 4-day program featured a blend of classroom and field learning, offering practical guidance and mentorship through workshops, expert talks, and personalized coaching, alongside a guided visit to SEKEM’s organic biodynamic farms. Fifteen teams will advance to the fully sponsored acceleration program that combines business training with technical assistance, utilizing a multimodal learning approach. This comprehensive program will offer entrepreneurial guidance, networking opportunities for product validation, investor readiness sessions, and technical assistance from matched CGIAR scientists. This program will conclude with the Demo Day in December 2024, where teams will pitch their solutions to a Selection Committee and network with researchers, industry experts, investors, and agribusinesses.